Communicative model as an institutionalization factor for a local self-government in the Russian Federation: By the example of local self-government bodies in the Republic of Tatarstan - Fatikhova, Diana Rustеmovna; Ziiatdinova, Elmira Mansurovna (Linguistics and Culture Review, 2021)
The paper investigates the communicative model’s influence on the local self-government development in Russia. The research’s relevance lies in the role of communication in the institutionalization of local government in Russia and is determined by the weakness inherent in local government institutions here. The nature of local self-government in the Russian Federation is contradictory. Local self-government bodies are closely connected with the state power and dependent on it, and at the same time, they are legally excluded from the system of state power bodies. The internal political events of the first half of 2020 indicate a new turn in the development of local self-government in the Russian Federation. According to the amendments to the Constitution of the Russian Federation adopted following the referendum of July 1, 2020, local self-government and state authorities are part of the unified public authority system in the Russian Federation, while at the same time local self-government bodies may be vested with certain state powers, provided that the material and financial resources necessary for the exercise of such powers are transferred to them. The implementation of the delegated powers to local self-government bodies is controlled by the state.